Judith Butler and the Deconstruction of the Cartesian Subject - Castelar, Andrés (Rastros Rostros, 2012)
This article starts from the ongoing research “Collective Identities and Recognition” being developed since 2008 in the research group “Ethics and Political Philosophy Praxis” of the Faculty of Humanities of the Universidad del Valle. This paper reviews the pertinence of the Cartesian subject from the proposal of the North American Judith Butler, especially for the discussion held with Slavoj Zizek about the relevance of said concept. This paper reviews the relevance of the use of the term postmodernism from the understanding of authors such as Butler and her theory of the non-elimination of the subject as a concept.
Keywords: deconstruction; political philosophy; ontology; postmodernism; subject